Sunitinib in patients with pancreatic neuroendocrine tumors: update of safety data. (31st January 2019) - Valle, Juan W; Borbath, Ivan; Rosbrook, Brad; Fernandez, Kathrine; Raymond, Eric
Aim: To describe the long-term safety of sunitinib in patients with progressive, well-differentiated, advanced/metastatic pancreatic neuroendocrine tumors.Patients & methods: Sunitinib- and placebo-treated patients from the Phase III study continued to receive sunitinib (37.5 mg on a continuous daily-dosing regimen) in two open-label extension studies.Results: Median (range) treatment exposure: 30.2 (0.7–269.4) and 87.1 (3.9–319.4) weeks for medium-term (n = 41) and long-term-treated (n = 61) populations, respectively. All patients experienced ≥1 adverse event (AE); 47 (45.6%) reported serious AEs. Common all-causality AEs: diarrhea (63.1%); neutropenia (43.7%); abdominal pain (40.8%). Fifteen (14.6%) patients discontinued treatment due to treatment-related AEs.Conclusion: The safety of extended sunitinib treatment was consistent with the known safety profile of sunitinib in pancreatic neuroendocrine tumors.